Prevalence Of Gastrointestinal Parasites Of Semi-Captive Orangutans (Pongo Pygmaeus) In Bukit Merah Orang Utan Island, Perak, Malaysia - Saad, Nurulanis Safia (2019)
This study was conducted to examine the prevalence of gastrointestinal parasites in twenty-one semi-captive orangutans (Pongo pygmaeus) in Bukit Merah Orang Utan Island, Perak. Samples were collected twice monthly with three replicates in period of one year (December 2014-December 2015). Five methods were used to screen for gastrointestinal parasites, protozoan parasites and parasitic eggs of worm.